Investigation of Impact of Temperature on Proposed Device with Reference to DIEL CYCLE (International Journal of Innovative Research in Computer Science & Technology, 2023)
A Proposed device designed to protect the  crops not only from the birds but also it is equipped with  the multiple sensors to sense and repel the wild animals also  from the cropland. It is also designed to sense any kind of  fire around the cropland. It can also sense the moisture level  of soil and alarm the farmers about it if moisture level goes  down or high. In this research paper we have done an  experiment to check the effect of temperature on this  device. We have kept this device under various  environments with different temperature and keep on  observing it 24 hours. This DIEL cycle of 24 hours in  various temperatures shows the effects of temperature on  this designed model. We have clearly found out the effects  of temperature on this device and can work efficiently in  our region. We can also extend this experiment in various  regions of country also. For this experiment, we have  chosen our local area of Ara, Bihta and Patna. We have  tried to find out the difficulties in working environment of  this device.
Keywords: Temperature impact; sensors; DIEL cycle; Wild Animal Attack; Repelling of Animal; Crop Protection